Combined effect of Cinnamomum zeylanicum blume essential oil and nystatin on strains of non-albicans Candida - Ricardo Dias Castro; Alessandro Leite Cavalcanti; Edeltrudes de Oliveira Lima
Introduction: considering the emergence of resistant species of albicans and non-albicans Candida to agents therapeutically available as a result of the increased number of immunocompromised population and of the increasingly frequent use of prophylaxis and empirical treatment with antifungals, it's verified that there is a clear and emerging need to introduce new antimicrobials agents in the therapeutic arsenal. The purpose of this study was to evaluate the antifungal activity of essential oil of Cinnamomum zeylanicum Blume alone and combined with Nystatin on strains of C. tropicalis and C. krusei. Methods: this was an experimental research in laboratory. It was determined the Minimum Inhibitory Concentration, using the microdilution method, as well as the Fractional Inhibitory Concentration to determine the possible synergistic effects of the association. Strains of C. tropicalis ATCC 40147 and C. krusei ATCC 40042 were used in the tests. When assessed separately, C. zeylanicum essential oil and Nystatin presented Minimum Inhibitory Concentration of 312,5 µg/mL and 64 µg/mL, respectively, on both tested strains. Results: When combined, were found Minimum Inhibitory Concentration of 39 µg/mL and 32 µg/mL for the essential oil and for Nystatin, respectively. The Fractional Inhibitory Concentration value was 0,6024 for both tested strains, indicating additivity of the inhibitory effect on fungal growth. Conclusions: the results indicate that C. zeylanicum essential oil has antifungal activity against the strains of non-albicans Candida evaluated and that its association with Nystatin potentiates this effect.